Improving Listening Skill Through Podcasts: The Students’ Perception - Ali, Nurbaiti; Losi, Rizky Vita; Tasril, Virdyra; Rizki, Amaral Aulia (JETLi: Journal of English Teaching and Linguistics, 2024)
Students' limited understanding of classroom lessons or materials can hinder their English language development. Additionally, in Indonesia, students rarely have opportunities to practice English, and teachers often do not use effective methods or real-life resources for teaching listening. However, with recent technological advancements, English is increasingly becoming the second language of choice, as it is widely used in all technology-related fields. This research purposed to reveal the students’ perception to use podcasts in the classroom. A descriptive quantitative approach was used and a questionnaire was administered to thirty students of SMAN 2 Binjai participating in the questionnaire in order to fully investigate their points of view. The research result revealed that students' perspectives regarding the accessibility and novelty of podcasts. The majority (90%) expressed agreement with the implementation of podcasts at class. Similarly, 86.67% agreed with the ease of using podcasts anytime and anywhere. The use of podcasts demonstrated a positive impact on students' listening skills. These findings underscored the students’ perception in utilizing podcasts effectively. Students believed that podcasts could improve their listening and speaking skills. Students expressed that using podcasts was enjoyable because it allowed them to enhance their skills while also learning about topics that interested them. However, challenges in effectively using podcasts in the classroom emerged, highlighting the need for further exploration of optimal implementation strategies.